The Physician Mentored Implementation Model. (March 2015) - Li, Jing; Hinami, Keiki; Hansen, Luke O.; Maynard, Gregory; Budnitz, Tina; Williams, Mark V.
<x xml:space="preserve">Abstract</x> Quality improvement (QI) efforts hold great promise for improving care delivery. However, hospitals often struggle with QI implementation and fail to sustain improvement in either process changes or patient outcomes. Physician mentored implementation (PMI) is a novel approach that promotes the success and sustainability of QI initiatives at hospitals. It leverages the expertise of external physician mentors who coach QI teams to implement interventions at their local hospitals. The PMI model includes five core components: (1) a hospital self-assessment tool, (2) a face-to-face training session including direct interaction with a physician mentor, (3) a guided continuous quality improvement and systems approach, (4) yearlong individual physician mentoring, and (5) a learning community supported by a resource center, listserv, and webinars. Mentors provide content and process expertise, rather than offering "one-size-fits-all" technical assistance that might not be sustained after the mentoring year ends. Mentors support and motivate QI teams throughout the planning and implementation phases of their interventions, help to engage hospital leadership, garner local physician buy-in, and address institutional barriers. Mentors also guide hospitals to identify opportunities for the adaptation and customization of original evidence-based models of care while ensuring the fidelity of those models. More than 350 hospitals have used the PMI model to implement successful national and statewide QI initiatives. Academic medical centers are charged with improving the health of patients and reengineering care delivery; thus, they serve as the ideal source for physician mentors and can act as leaders in implementing QI projects using the PMI model.